2011
DOI: 10.1371/journal.pone.0021108
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Gap Junction Hemichannel Suppresses Disease Progression in Mouse Models of Amyotrophic Lateral Sclerosis and Alzheimer's Disease

Abstract: BackgroundGlutamate released by activated microglia induces excitotoxic neuronal death, which likely contributes to non-cell autonomous neuronal death in neurodegenerative diseases, including amyotrophic lateral sclerosis and Alzheimer's disease. Although both blockade of glutamate receptors and inhibition of microglial activation are the therapeutic candidates for these neurodegenerative diseases, glutamate receptor blockers also perturbed physiological and essential glutamate signals, and inhibitors of micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(134 citation statements)
references
References 65 publications
7
123
0
1
Order By: Relevance
“…Activated HCs have been involved in the release of gliotransmitters such as ATP and glutamate as well as chemokines that have deleterious consequences on neurons as reported in murine models of AD [18][19][20], experimental allergic encephalomyelitis [21], amyotrophic lateral sclerosis [20,22] and neuropathic pain [23,24]. In our study, it has also been demonstrated that activated HCs can allow Ca 2+ influx, contributing to a maintenance of high [Ca 2+ ]i.…”
Section: Commentarysupporting
confidence: 73%
“…Activated HCs have been involved in the release of gliotransmitters such as ATP and glutamate as well as chemokines that have deleterious consequences on neurons as reported in murine models of AD [18][19][20], experimental allergic encephalomyelitis [21], amyotrophic lateral sclerosis [20,22] and neuropathic pain [23,24]. In our study, it has also been demonstrated that activated HCs can allow Ca 2+ influx, contributing to a maintenance of high [Ca 2+ ]i.…”
Section: Commentarysupporting
confidence: 73%
“…Furthermore, we evaluated axonal injury by SMI31 immunostaining. Previously, we reported that bead-like swelling along axons (axonal beading) is a good pathological marker of axonal injury resulting from axonal transport impairment (27)(28)(29). The reduction in axonal beading is associated with recovery from EAE (30).…”
Section: A Single Injection Of Shed-cm Ameliorates the Clinical Severmentioning
confidence: 99%
“…ATP and glutamate significantly inhibited SR-101 and PI uptake. In contrast, an in vivo BBB-permeable analog of GA INI-0602, which has been reported to inhibit Cx32-mediated glutamate release from microglial cells (Takeuchi et al, 2011), increased SR-101 and PI uptake. Addition of 1.4 mM CaCl 2 in the Ca 21 -free ECF buffer significantly reduced the enhanced uptake of SR-101 and PI.…”
mentioning
confidence: 89%